Criminal Jurisdiction of Securities Court in Ngeria: Panacea for Delayed Market Justice (Global Journal of Management and Business Research, 2018)
A near-utopian adjudicatory architecture is an eminent pillar for assessing enforcement of contract in any jurisdiction as captured by the World Bank Index of Ease of Enforcing Contract Nigeria is one of the climes with securities court for adjudicating capital market disputes even though is clogged with adjudicatory forum controversy with the Federal High Court The essence of establishing the Investment and Securities Tribunal IST is to fastrack quick dispensation of securities disputes to enhance pool of investment opportunities into the Nigerian market However the IST can only adjudicate on civil securities matters it does not have jurisdiction on genre of securities crimes which fall within the exclusive judicial forum of the High Court It has been keenly observed that securities investors are lamenting delays in adjudication of securities crimes which litter the High Court dockets and this is seriously declining investors confidence and the growth of securities market in Nigeria This article aims at examining the consequences of delay in adjudication of securities crimes by the Federal High Court on the investors and the Nigerian economy The article therefore advocates for constitutional imprimatur by listing the IST among superior court in Nigeria clothed with both civil and criminal jurisdictions to enhance the peculiarity of securities torts and crimes adjudication phase out the delays often experienced at the High Court by remitting securities crime cases at the IST It finally exemplifies the practical structure of criminal jurisdiction of the IST and how it will develop our criminal securities jurisprudence in the cynosure of mega investors and various jurisdictions of the world
Keywords: criminal jurisdiction; securities court; panacea and market justice